“Through their own efforts”: Nutrition Studies and Interventions in Early 20th-Century Northern Newfoundland and Southern Labrador - Hanrahan, Maura (Cuizine, 2016)
A small but significant spate of health and nutrition studies was completed in Northern Newfoundland and Southern Labrador in the first third of the 20th century. Published in peer-reviewed journals, such as the Journal of the American Medical Association and the Irish Journal of Medical Sciences, the research was sponsored by the International Grenfell Association (IGA), led by zealous Christian missionary and physician Wilfred Grenfell. The paper contributes to Canadian food studies by providing insights into the challenging social and economic conditions faced by the people of the region and the persistence of European food ways, despite the vastly different geophysical setting. It demonstrates that the studies had widespread impacts as they advanced the understanding of deficiency diseases. Yet the interventions had limited local benefits and were not generally successful over time. In keeping with contemporary approaches, the IGA’s nutrition research restricted community development by maintaining and institutionalizing patron-client relationships. This methodology likely led to missed opportunities in terms of community health and development.